Assessing the vulnerability of women to sexually transmitted diseases STDS/ HIV: construction and validation of markers - Mónica Cecilia De la Torre Ugarte Guanilo (Revista da Escola de Enfermagem da USP, 2014)
Objective To construct and validate markers of vulnerability of women to STDs/HIV, taking into consideration the importance of STDs/HIV. Method Methodological study carried out in three stages: 1) systematic review and identification of elements of vulnerability in the scientific production; 2) selection of elements of vulnerability, and development of markers; 3) establishment of the expert group and validation of the markers (content validity). Results Five markers were validated: no openness in the relationship to discuss aspects related to prevention of STDs/HIV; no perception of vulnerability to STDs/HIV; disregard of vulnerability to STDs/ HIV; not recognizing herself as the subject of sexual and reproductive rights; actions of health professionals that limit women’s access to prevention of STDs/HIV. Each marker contains three to eleven components. Conclusion The construction of such markers constituted an instrument, presented in another publication, which can contribute to support the identification of vulnerabilities of women in relation to STDs/HIV in the context of primary health care services. The markers constitute an important tool for the operationalization of the concept of vulnerability in primary health care and to promote inter/multidisciplinary and inter/multi-sectoral work processes.